A multilayered nanofibrous patch functionalized with adipose tissue extract for the treatment of bladder regeneration. (August 2022) - Wang, Jing; Feng, Chunxiang; Zhu, Yunpeng; Wang, Zhixian; Ren, Xiang; Li, Xing; Ying, Yisheng; Tian, Yiqun; Yu, Kai; Liu, Shiliang; Liu, Chang; Zeng, Xiaoyong
Graphical abstract: Highlights: ATE, a complex of various cytokines, could promote angiogenesis and maintain stem cell pluripotency. We integrates PLCL electrospun microfibers and ATE/HA colloidal solution to constitute a hierarchical nanofibrous patch. The patches could achieve the bionic reconstruction by providing a stable mechanical microenvironment and important biochemical factors. Abstract: Bladder tissue engineering is a promising approach to generating new tissues to replace damaged or diseased organs, breaking the limitations of current therapies using reconfigured autogenous bowel segments. Adipose tissue extract (ATE) is a non-cellular three-dimensional macromolecular network that provides an appropriate local microenvironment for cells and affects cellular metabolism, proliferation, differentiation, or organoid formation. This study integrated electrospun nanofibers mats and hyaluronic acid colloidal solution to constitute a multilayered nanofibrous patch, where ATE was added as a biological additive. In vitro study, we observed an increase in the pluripotent marker proteins (Oct-4, Sox-2, and Nanog) of adipose-derived stem cells (ADSCs) and bone mesenchymal stem cells (BMSCs) when cultured with ATE. The CCK-8 test, scratch assay, transwell migration assay, and tube formation assay demonstrated the positive effect of ATE on endothelial cells (ECs) proliferation, migration, and angiogenesis. The feasibility and effectiveness of the patch were investigated in a rat bladder defect model. The primary ideal results revealed the patches' great potential for tissue engineering repair and regenerative medicine.